Soluble urokinase plasminogen activator receptor (suPAR) levels predict damage accrual in patients with recent-onset systemic lupus erythematosus. Issue 106 (January 2020) - Enocsson, Helena; Wirestam, Lina; Dahle, Charlotte; Padyukov, Leonid; Jönsen, Andreas; Urowitz, Murray B.; Gladman, Dafna D.; Romero-Diaz, Juanita; Bae, Sang-Cheol; Fortin, Paul R.; Sanchez-Guerrero, Jorge; Clarke, Ann E.; et al.
Abstract: Objective: The soluble urokinase plasminogen activator receptor (suPAR) has potential as a prognosis and severity biomarker in several inflammatory and infectious diseases. In a previous cross-sectional study, suPAR levels were shown to reflect damage accrual in cases of systemic lupus erythematosus (SLE). Herein, we evaluated suPAR as a predictor of future organ damage in recent-onset SLE. Methods: Included were 344 patients from the Systemic Lupus International Collaborating Clinics (SLICC) Inception Cohort who met the 1997 American College of Rheumatology classification criteria with 5-years of follow-up data available. Baseline sera from patients and age- and sex-matched controls were assayed for suPAR. Organ damage was assessed annually using the SLICC/ACR damage index (SDI). Results: The levels of suPAR were higher in patients who accrued damage, particularly those with SDI≥2 at 5 years (N = 32, 46.8% increase, p = 0.004), as compared to patients without damage. Logistic regression analysis revealed a significant impact of suPAR on SDI outcome (SDI≥2; OR = 1.14; 95% CI 1.03–1.26), also after adjustment for confounding factors. In an optimized logistic regression to predict damage, suPAR persisted as a predictor, together with baseline disease activity (SLEDAI-2K), age, and non-Caucasian ethnicity (model AUC = 0.77). Dissecting SDI into organ systems revealed higher suPAR levels in patients who developed musculoskeletal damage (SDI≥1; p = 0.007). Conclusion: Prognostic biomarkers identify patients who are at risk of acquiring early damage and therefore need careful observation and targeted treatment strategies. Overall, suPAR constitutes an interesting biomarker for patient stratification and for identifying SLE patients who are at risk of acquiring organ damage during the first 5 years of disease. Graphical abstract: Image 1 Highlights: Serum levels of suPAR predicted future global organ damage in newly diagnosed cases of SLE. Future musculoskeletal damage was significantly associated with baseline suPAR when organ domains were studied separately. The predictive value of suPAR was independent of known risk factors for organ damage development. suPAR was not associated with disease activity or disease phenotypes.